2005
DOI: 10.1590/s1517-83822005000100018
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Metarhizium anisopliae against immature stages of Anastrepha fraterculus fruitfly (Diptera : Tephritidae)

Abstract: The study evaluated the effectiveness of Metarhizium anisopliae var. anisopliae (Hyphomycetes : Moniliales) strain E9, isolated from the pasture spittlebug Deois flavopicta (Hemiptera : Cercopidae), against larvae, prepupae and pupae stage and emergent adults of Anastrepha fraterculus, the South American fruitfly. The bioassay was carried out simulating field conditions, on autoclaved (AS) and non-autoclaved (NAS) soil from typical citrus orchards in the State of São Paulo, Southeastern region of Brazil. Vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 5 publications
0
15
0
2
Order By: Relevance
“…Entomopathogenic fungi: Many studies have been conducted on the control of C. capitata , Anastrepha fraterculus , A. ludens , B. oleae and B. tryoni with different entomopathogenic fungi [125,126,127,128,129,130,131,132,133,134,135,136,137,138,139]. Yee and Lacey [140] demonstrated that adult western cherry fruit flies ( R. indifferens ) are susceptible to Metharizium anisopliae .…”
Section: Life History R Cerasimentioning
confidence: 99%
“…Entomopathogenic fungi: Many studies have been conducted on the control of C. capitata , Anastrepha fraterculus , A. ludens , B. oleae and B. tryoni with different entomopathogenic fungi [125,126,127,128,129,130,131,132,133,134,135,136,137,138,139]. Yee and Lacey [140] demonstrated that adult western cherry fruit flies ( R. indifferens ) are susceptible to Metharizium anisopliae .…”
Section: Life History R Cerasimentioning
confidence: 99%
“…anisopliae, isolated from Deois flavopicta (Hemiptera:Cercopidae), obtained from a stock collection of the Department of Genetics and Evolution, Universidade Estadual de Campinas, Campinas, São Paulo, Brazil. This strain is largely used in bioassays and genetic studies (9,11,20,23,32). The conidia used in these studies were producted on complete culture medium (CM) consisting of yeast extract, glucose, minerals, agar, and water, according to Alves et, 1998 (3).…”
Section: Strain Of M Anisopliaementioning
confidence: 99%
“…Adults of both tropical and temperate tephritids are susceptible to a number of hypocralean entomopathogenic fungi, including Beauveria bassiana (Balsamo) Vuillemin, with the infections generally resulting in high fly mortality as well as reduced fecundity, and modified mating behavior (Carswell et al, 1998;Castillo et al, 2000;de La Rosa et al, 2002;Dimbi et al, 2003Dimbi et al, , 2009Destéfano et al, 2005;Yee and Lacey, 2005;Quesada-Moraga et al, 2006;Toledo et al, 2007;Sookar et al, 2008;Daniel and Wyss, 2009). Within the Rhagoletis species, Yee and Lacey (2005) found adult R. indifferens to be highly susceptible to Metarhizium anisopliae (Metschnikoff) Sorokin, while Daniel and Wyss (2009) found adults of the closely related European cherry fruit fly, Rhagoletis cerasi Loew, to be susceptible to six fungus isolates from species that included B. bassiana and M. anisopliae.…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory exposures of last instar tropical Ceratis and Anastrepha species (Diptera: Tephritidae) to M. anisophilae and B. bassiana have generally resulted in high infection rates, evidenced by mycosis in the pupal stage and reduced adult emergence (Lezama-Gutiérrez et al, 2000;Ekesi et al, 2002;Destéfano et al, 2005;Mochi et al, 2006;Quesada-Moraga et al, 2006). Fewer hypocralean entomopathogenic fungi susceptibility studies have been conducted using preimaginal temperate tephritid hosts because these species are mostly univoltine, difficult to colonize, and there is a narrow time period in which to obtain wild pre-pupal larvae after they exit the fruit and before they pupate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation